The Moment of Mobilization: The Legislative Consequences of Trans Rights Mobilization in Sweden, Norway, and Finland - Alaattinoğlu, Daniela (Routledge, 2025)
Trans rights defenders have mobilized legally and politically to change oppressive laws and practices since at least the early 2010s. Both global and Nordic, this trend remains underexplored by scholars. The article at hand compares the legislative outcomes of such mobilization with reference to Sweden, Norway, and Finland. By examining legal gender recognition and trans legal parenthood through legal doctrinal, legal mobilization, and comparative modes of analysis, I argue that in the Nordic region three key aspects determine whether legislation is passed that respects trans people’s personal integrity and their right to private and family life. The first aspect is the timing of mobilization in relation to the available supranational and transnational rights norms, with later mobilization benefiting from more developed rights frameworks. The second is how trans rights have been politicized in the countries under comparison; politicization can either promote or hinder legislative change. The third is the form of mobilization, particularly the use of strategic mobilization by some trans rights defenders. In this respect, it appears that legislation created in the aftermath of strategic litigation has been less comprehensive than legislation advanced mainly through political mobilization.